Risk and Protective Factors in the Provision of Academic and Psychosocial Support for Refugee Adolescents in Greece: The Case of the Skaramagas Learning Center - Adamopoulou, Eirini; Papadatou-Pastou, Marietta; Konstantinidi, Evangelia Styliani (Refuge, 2025)
This study examines the perceptions of students, parents, and teachers regarding the protective and risk factors involved in providing academic and psychosocial support to refugee adolescents through a nonformal education program in a temporary accommodation facility in Greece. A thematic analysis of focus groups reports highlights the importance of creating opportunities for meaningful participation, the critical role of teacher–student empowering relationships, the challenges of navigating socio-cultural barriers, and operational difficulties inherent in emergency education settings. Findings emphasize the complex interaction between individual circumstances and contextual factors essential in promoting resilience among refugee adolescents in transitional settings.